PENURUNAN PARAMETER KEKERUHAN, TSS DAN TDS DENGAN VARIASI UNIT FLOKULASI - Edhi Sarwono; Khairunnisa Rizky Aprillia; yunianto Setiawan (Jurnal Teknologi Lingkungan UNMUL, 2017)
AbstractA research on water treatment at Mahakam River water using the gravel bed flocculator (medium grained), the variation of theflocculation units gravel bed using granular media are used in the form of pieces of PVC pipe 1 "by 2cm, while flocculation with baffles chanel uses glass barriers on flokulasinya unit. Pieces of PVC pipe is functioned as the space between the grains of the media used as column streams that meander which is expected to be a medium for colloids that have terdestabilisasi of coagulation process will be in contact with the joining form a floc with a larger size and can be deposited, while the variation unit flocculation receipts baffle channel, where the unit of flocculation, there are the glass partition in the unit, the bulkhead is intended as a slow stirring in units flocculation to produce water movement that encourages contact between the particles without causing a rupture of a combination of particles that have been formed. The parameters examined, ie, turbidity, TSS and TDS. Retrieved onturbidity removal efficiency of gravelbed 54.34% and of amounted to 80.41%baffles,for TSS removal efficiency with gravelbed 39.82% and baffles 59.33%, and for the efficiency of TDS decrease by gravelbed 14.28% with baffles by 106 , 25%.  Keyword: Gravelbed, BaffleChanel, coagulation, flocculation, sedimentation